E-SAS liveworksheet with individualized learning for intellectual disabilities in chemistry law: Analysis of profiles and learning outcomes - Amelia Aura Trisiawati; Yulina Dewi Sartika; Rahmania Fitrah Sari; Muchlis Muchlis; Dian Novita (Education and Development Research, 2025)
This research aims to fill the research gap by combining in-depth analysis of learning profiles and measurement of learning outcomes for students with intellectual disabilities through E-SAS Liveworksheet with individualized learning on chemical law materials, especially Lavoisier's law and Dalton's law. This research involved 3 students with mild intellectual disabilities at Senior High School 10 Surabaya. This study used an embedded mixed-method design. Observations and interviews were used to collect qualitative data. Learning outcomes were used for collecting quantitative data. Qualitative data were analyzed using thematic analysis and matrix coding query with NVivo 11. Quantitative data were analyzed through the N-gain test on pretest and posttest scores. The study's findings indicate that when analyzing learning profiles, each student with intellectual disabilities has unique and diverse learning skills and styles. Learning skills include self-regulation, technology interaction, and information processing skills. Students' learning styles show the preferences of each student in the visual, auditory, and kinesthetic. The improvement in learning outcomes is indicated by the acquisition of an average N-gain score of 0.9 with high criteria. These research results demonstrate the importance of understanding the diversity of student learning profiles when creating learning processes and media, thereby creating effective learning impacting their learning outcomes.